Association Between Nursing Diagnoses and Mortality in Hospitalized Patients with COVID-19: A Retrospective Cohort Study - José Ángel Hernández-Mariano; Olivia Mendoza-Macario; María del Carmen Velázquez-Núñez; María del Carmen Cedillo-Ordaz; Blanca Estela Cervantes-Guzmán; Dulce Milagros Razo-Blanco-Hernández; Erick Alberto Landeros-Olvera; Fani Villa-Rivas; Rocío Castillo-Díaz; Guillermo Cano-Verdugo (Nursing Reports)
Previous studies suggest that nursing diagnoses (NDs) could predict clinical outcomes, such as mortality, among patients with non-communicable diseases. However, evidence in patients with COVID-19 is still scarce. Objective: To evaluate the association between NDs and COVID-19 mortality among hospitalized patients. Methods: A retrospective cohort study was conducted on 498 paper clinical records of patients hospitalized for at least 72 h in the internal medicine unit for COVID-19 from June to December 2020. The interest association was assessed using logistic regression models. Results: NDs focused on COVID-19 pulmonary responses, such as impaired gas exchange (OR = 3.04; 95% CI = 1.87, 4.95), impaired spontaneous ventilation (OR = 3.67; 95% CI = 2.17, 6.21), or ineffective airway clearance (OR = 2.47; 95% CI = 1.48, 4.12), were significant predictors of mortality. NDs on COVID-19 extrapulmonary responses, such as risk for unstable blood glucose level (OR = 2.45; 95% CI = 1.45, 4,15), risk for impaired liver function (OR = 2.02; 95% CI = 1.11, 3.63), hyperthermia (OR = 2.08; 95% CI = 1.29, 3.35), decreased cardiac output (OR = 2.95; 95% CI = 1.42, 6.11), or risk for shock (OR = 3.03; 95% CI = 1.28, 7.13), were associated with a higher risk of in-hospital mortality. Conversely, patients with NDs of fear (OR = 0.56; 95% CI = 0.35, 0.89) and anxiety (OR = 0.44; 95% CI = 0.26, 0.77) had a lower risk of death. Conclusions: NDs on pulmonary and extrapulmonary responses to COVID-19 were associated with in-hospital mortality, suggesting that they are indicators of the severity of these patients. Therefore, NDs may help nursing staff identify individuals who require closer monitoring and guide early interventions for their recovery.